Immunosenescence is associated with human cytomegalovirus and shortened telomeres in type I bipolar disorder. (10th September 2013) - Rizzo, Lucas Bortolotto; Do, Carine Hartmann; Grassi‐Oliveira, Rodrigo; Wieck, Andréa; Correa, Bruna Luz; Teixeira, Antonio Lucio; Bauer, Moisés Evandro
<x xml:space="preserve">Abstract</x> Objective Bipolar disorder (BD) has been associated with persistent low‐grade inflammation and premature cell senescence, as shown by reduced telomere length (TL). The human cytomegalovirus (CMV) has increasingly been implicated in accelerated immunosenescence in aging studies. Here, we compared CMV serology and its relationships with cell senescence markers, including TL and lymphocyte subsets, in patients with type I BD and healthy controls. Methods Twenty‐two euthymic female patients with BD type I and 17 age‐matched healthy controls were selected for the study. A sample of blood was collected and mononuclear cells and DNA were isolated and TL measured. CMV immunoglobulin M (IgM) and IgG titers were measured using chemiluminescent assays. Lymphocyte subsets [T, natural killer (NK) and NKT] were phenotyped by flow cytometry. Results Individuals with BD had shorter TLs but higher CMV IgG levels than controls (both p < 0.01). CMV IgG level was inversely correlated with TL. None of the subjects showed IgM reactivity for CMV, excluding acute viral infection. CMV IgG level was associated with expansion of senescent CD8+CD28− T cells and NK cells, which are involved in viral control. Conclusions These data support the hypothesis of accelerated aging in BD, as shown by shortened telomeres, higher seropositivity for CMV, and expansion of senescent T cells.